Risk management plan for slope repair using Terralink Construction Method alligning sustainable environment / Muhamad Afiq Al-Amin Mohd Kabri - Mohd Kabri, Muhamad Afiq Al-Amin (Universiti Teknologi MARA (UiTM), 2025)
Risk management plays a pivotal role in safeguarding the success and safety of construction projects, particularly for slope repair works involving innovative methods. In Malaysia, the Terralink Construction Method was the new method used for the slope repair project at Simpang Pulai-Blue Valley Road. However, there is no existing risk management plan for the Terralink Construction Method. Hence, this study focuses on the Terralink Construction Method, a newly adopted technique in Malaysia, and aims to develop a risk management plan for slope repair using the Terralink Construction Method. The research objectives include identifying hazards inherent to this method, analysing associated risks, and developing a risk management plan that aligns with regulatory directives under Arahan KPKR 29/2023.